CONSUMER PROTECTION AGAINST GHOST SELLERS IN THE SHOPEE MARKETPLACE FROM THE PERSPECTIVE OF LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION AND COMPILATION OF SHARIA ECONOMIC LAW - Nur Roudoh Harahap; Uswatun Hasanah (Program Pascasarjana UIN Sumatera Utara, 2025)
The rapid development of information technology has driven the emergence of various forms of electronic commerce (e-commerce), including marketplace platforms such as Shopee. This online transaction model has transformed the interaction between sellers and buyers into a non-face-to-face system, thus creating new complexities in the legal relationship between businesses and consumers. Amidst this progress, the phenomenon of ghost sellers has emerged, namely fictitious sellers (fake store accounts) who are irresponsible and misuse the platform's identity and system to deceive consumers, one of which is by sending goods that do not match the description or not sending goods at all. This phenomenon is increasingly widespread with the increase in digital transactions on e-commerce platforms, especially during major promotional events such as Harbolnas and Ramadan Sale. This study aims to examine the analysis of ghost seller practices in the Shopee marketplace, the form of consumer protection for ghost sellers in the Shopee marketplace from the perspective of Law Number 8 of 1999 concerning Consumer Protection and the Compilation of Sharia Economic Law, as well as Shopee's responsibility for losses experienced by consumers. This study uses a normative method with a statutory approach and a study of Islamic legal literature to analyze the responsibilities of businesses and protection of consumer rights. The results of the study indicate that the form of consumer protection that is harmed by ghost sellers on the Shopee platform is related to violations of the provisions of Articles 4, 7, 8 and 19 of the Consumer Protection Law (UUPK) which guarantees consumers' rights to comfort, security, correct and honest information, and products that comply with the agreement, and are prohibited in the KHES because they contain elements of fraud (tadlis) and ambiguity (gharar) as regulated in articles 22, 23, and 24 of the KHES. On the other hand, Shopee is responsible for consumer losses by providing protection through a complaint system, Shopee guarantee and a refund mechanism if the item does not match the description. However, if the transaction is carried out outside the official Shopee system, the loss is the responsibility of the consumer. Therefore, both in positive law and Islamic economic law, consumer protection is an obligation that must be enforced to maintain trust and fairness in online transactions.